An Efficient Synthesis of Rivaroxaban. Issue 4 (26th January 2023) - Lin, Xiaoyu; Li, Nanlian; Zhu, Chenlong; Sun, Bingfeng
Abstract: An efficient synthesis of rivaroxaban has been accomplished by a sequence spanning five steps from 4‐morpholinoaniline and ( S )‐2‐(oxiran‐2‐ylmethyl)isoindoline‐1, 3‐dione with an overall yield of 44 %. This synthesis is concise, environmentally benign and cost‐effective, providing a good basis for the development of a new process for rivaroxaban. Abstract : An efficient synthesis of rivaroxaban has been accomplished, which delivers a short synthetic sequence containing five successive reactions from 4‐morpholinoaniline (3 ) and ( S )‐2‐(oxiran‐2‐ylmethyl)isoindoline‐1, 3‐dione (4 ) with an overall yield of 44 %. Featuring a late‐stage oxidation strategy, the construction of the morpholin‐3‐one was executed in the last step on the highly functionalized substrate ( S )‐5‐chloro‐ N ‐((3‐(4‐morpholinophenyl)‐2‐oxooxazolidin‐5‐yl)methyl)thiophene‐2‐carboxamide (14 ) with the thiophene ring intact.